Digital marketing for optimizing the bamboo handicrafts marketing in IKM ‘Mandiri Bambu Craft’ - Diesyana Ajeng Pramesti; Latifatul Khoiriyah; Dhian Tri Antono; Dwi Asmoro; Octaviana Ayu Pratiwi; Muhamad Valdanu (Universitas Muhammadiyah Magelang, 2022)
Ngadiwinatan 1, Karanganyar, Borobudur, Magelang Regency is one of the craft’s areas that needs to be considered by the Government. Since the Covid-19 Pandemic, the Borobudur Temple Tourism Park has temporarily closed for visitors, so the craftsmen difficult to sell their products. The purpose of this service is optimizing digital marketing, in order to expand the market for handicrafts, as well as increasing the human resources of the IKM ‘Mandiri Bambu Craft’. The service implementation method is the Participatory Rural Appraisal (PRA) through socialization, FGD, training, and mentoring. The results are the regrouping of groups of craftsmen who are no longer active, making new craft products, the new IKM logo 'Mandiri Bambu Craft', and digital marketing development of IKM products.